MODEL PENGEMBANGAN PERAN SERTA MASYARAKAT BERBASIS KEARIFAN LOKAL DALAM OTONOMI DAERAH DAN IMPLIKASINYA TERHADAP KETAHANAN WILAYAH KOTA SURAKARTA - Muhammad Hendri Nuryadi (Jurnal Ketahanan Nasional, 2013)
This paper explained the effective and appropriate community participation model for the local characteristic which was expected to affected the embodiment of Surakarta city regional resilience as a city with short wheelbase and its plurality existence. Regional Autonomy implementation started in 1999 until 2012 as yet marginalized community’s rights as the implementer of the government’s policy. The qualitative data, regional autonomy concept, and regional autonomy showed community had an important role on autonomy implementation due to the people’s authority over state sovereignty.Keywords: Community’s Role, Local Wisdom, Regional Autonomy, and Regional Resilience.